Intellectual [dis]honesty in architecture - Masden II, Kenneth G.; Salingaros, Nikos A. (Journal of Architecture and Urbanism, 2014)
Many, if not a majority, of the world’s citizens view contemporary architecture as ineffective in accommodating the lives of everyday human beings. And yet, voluminous texts by prominent architects and the media argue just the opposite; that, in fact, flashy and expensive new projects profoundly benefit humanity. Those buildings supposedly provide continued advancement in how humans occupy the world. While there is no doubt that the built environment is instrumental to human achievement and wellbeing, what is the true value of the ill-formed, and perhaps ill-conceived, products of today’s leading architects? This essay argues that the elite power structure behind high-profile architectural projects is focused more upon promoting like-minded architects, and their narrow ideological interests, than in satisfying the ordinary everyday user. In doing so, this activity irrevocably damages the environment and markedly diminishes human neuro-physiological engagement with the man-made world. The logical conclusion from this purposeful misrepresentation is that the profession deliberately manipulates both the general public and architecture students to serve its own agenda.